Language variation in Sobat Ambyar movie: A sociolinguistic review - Wiyanti, Endang; Purnama, Syahfitri; Yanda , Abdulkarimu (BAHASTRA, 2025)
Language variation is an important linguistic phenomenon because it can show the social diversity of speakers and the function of language in social interaction. In the context of film, language variation can be a mirror of existing social and cultural dynamics and provide comprehensive sociolinguistic insights. The purpose of this study is to describe the forms of language variation found in the dialogue of Sobat Ambyar movie in order to understand the relationship between language variation and the social context behind it and its contribution to strengthening local cultural identity and authenticity of the film. This research approach uses a qualitative approach. The data were obtained by using listening and note-taking techniques, content analysis with descriptive presentation. The results of this study obtained six language variations namely acrolek, basilek, vulgar, colloquial, jargon, and ken in Indonesian and Javanese. The dominant findings of this study were vulgar, basilek, and acrolek, with 18, 13, and 14 findings, severally. The use of these language variations enriches the viewing experience and strengthens local cultural identity, making the film more authentic and close to the audience.